IMPLEMENTATION OF THE KURIKULUM MERDEKA IN NATURAL AND SOCIAL SCIENCE LEARNING TO STRENGTHEN ELEMENTARY STUDENTS' INDEPENDENCE - Fatonah, Siti; Chasanah, Uswatun; Lusiana, Lusiana (UIN Sunan Kalijaga Yogyakarta, 2023)
The school curriculum in Indonesia is constantly changing. It is currently a transitional period between the 2013 curriculum and the Kurikulum Merdeka. This study aims to analyze the implementation of the Kurikulum Merdeka in science learning to strengthen the learning independence of grade 4 elementary students. This research used a descriptive qualitative approach. The subjects in this study were the grade 4 teacher and students at Muhammadiyah Elementary School (MES) Kadisoka Yogyakarta. The data collection techniques used were interviews, observation, and documentation. The data analysis technique in this study used the data condensation, data display, and conclusion. The results of this study indicate that MES Kadisoka uses the Kurikulum Merdeka, but it has not been implemented in all classes, only in grade 1 and grade 4, whereas other classes are still implementing the 2013 Curriculum; Science learning seeks to provide understanding to students of how to identify various problems and find solutions to achieve a sustainable learning goal of training students' independence. Natural and social sciences aim to train students to think critically, have high curiosity, and try to realize the Project of Pancasila Student Profile Strengthening (PPSPS) in the Kurikulum Merdeka; The teacher's role in science learning is not only teaching and educating but also being a facilitator and evaluator, providing guidance, and encouraging creativity to maximize students' abilities.